Two-dimensional transition metal dichalcogenides and their heterostructures: Role of process parameters in top-down and bottom-up synthesis approaches. (1st March 2022) - Rani, Sonam; Sharma, Meenu; Verma, Deepak; Ghanghass, Anjali; Bhatia, Ravi; Sameera, I.
Abstract: In the recent years, two-dimensional (2D) transition metal dichalcogenides (TMDs) have received worldwide attention because of their peculiar and fascinating electronic properties at the atomic regime. The atomically thin TMDs are considered as the most promising candidates for the advanced electronic and optoelectronic devices due to their tunable band gaps and strong interaction with the light. Till date, over 40 TMDs that can be cleaved into 2D mono-layers from their bulk counterparts have been reported. Further, integration of TMDs into heterostructures with sharp edges, controlled orientation and band alignment, hosts new horizons for the study of correlated phenomena arising from the interactions and quantum confinement effects. The exotic physical properties and applications of TMDs and their heterostructures depend on their structural and electronic characteristics, which are strongly influenced by their synthesis approach. This review article aims to provide a holistic idea on the various methods for the synthesis of TMDs and their heterostructures. A critical review on the effect of various process parameters which determine the morphological and structural properties of TMDs has been presented. Highlights: An overview of top-down and bottom-up synthesis approaches of TMDs is presented. Recent advances in the growth of lateral and vertically stacked heterostructures are reviewed. Effect of process parameters on the structure and morphologies of TMDs has been elucidated. Potential of various synthesis techniques along with their future prospects has been summarized.